Microscopic study of human nasal cavity microanatomy using semi-thin resin embedding and methylene blue staining. (2nd January 2019) - Firat, Aysegul; Onerci-Celebi, Ozlem; Tuncel, Alican; Ergun, Mine; Hayran, Murvet
ABSTRACT: The nasal cavity is a part of the respiratory tract which humidifies, filters, and warms the air we breathe, as well as being the organ of olfaction. It is easily accessible in terms of morphological and histopathological evaluation for clinical and research purposes. There have been many studies and textbooks showing the histological evaluation of the nasal cavity's three functional regions: the vestibule, respiratory, and olfactory. The present study aimed to examine the nasal mucosa in a detailed manner in 11 predetermined anatomic areas. Specimens were collected from six fresh-frozen cadavers using a standard punch biopsy procedure. Microscopic evaluation was done on the nasal mucosa, glands, blood vessels, muscles, connective tissue, and neural anatomy. Also, examined and described were the epithelial cell and glandular transitions in the mucosal lining. The microscopic investigation of these features in the nasal cavity provided important information for both clinical and research purposes.